2015
DOI: 10.1111/cen.12793
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum osteocalcin level and visceral obesity in Chinese postmenopausal women

Abstract: The serum osteocalcin level was inversely correlated with the visceral fat content in these Chinese postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Interestingly, OC levels maintain their association with improved glucose tolerance and insulin secretion and sensitivity, independent of plasma adiponectin level [27]. The negative correlation between abdominal obesity and serum OC was confirmed by other studies in different ethnic groups [28,29].…”
Section: Osteocalcin Glucose and Lipid Metabolismsupporting
confidence: 57%
“…Interestingly, OC levels maintain their association with improved glucose tolerance and insulin secretion and sensitivity, independent of plasma adiponectin level [27]. The negative correlation between abdominal obesity and serum OC was confirmed by other studies in different ethnic groups [28,29].…”
Section: Osteocalcin Glucose and Lipid Metabolismsupporting
confidence: 57%
“…Maddaloni et al suggested that circulating OCN + monocytes could be a marker for vascular disease in diabetic patients [ 21 ]. Our previous studies found that a decreasing trend in serum OCN levels accompanied an increase in VFA, and VFA was inversely correlated with serum OCN levels [ 11 , 12 ]. Serum FGF23 levels were independently and positively correlated with the presence of lowerextremity atherosclerotic disease among Chinese patients with type 2 diabetes mellitus [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in human subjects have also revealed correlations between the levels of these hormones and obesity. Our previous studies reported significant positive correlations between both serum FGF23 and NGAL levels and obesity [ 9 , 10 ], whereas serum OCN levels were significantly inversely correlated with obesity [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Study characteristics for 21 eligible studies are summarized in ▶table 1. Studies were conducted on both healthy subjects and pa-tients, including 8 on healthy people [27,31,[36][37][38][39][40], 6 on post-menopausal women [37,[41][42][43][44][45], 3 on those with coronary heart disease [36,39,46], 3 on patients with type 2 diabetes [47][48][49], and 1 on women with polycystic ovary syndrome [50]. Four studies provided data for two different type of participants separately [31,36,37,39].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The quality of the included studies varied from 5-8 points on 10-point Newcastle-Ottawa scale. Seven studies scored 8 stars [27,37,40,42,44,48], five studies scored 7 stars [38,39,43,45], 7 studies scored 6 stars [36,41,46,47,49,50] and 2 studies scored 5 stars [31]. The age range of studies was between 18-69 years old.…”
Section: Study Characteristicsmentioning
confidence: 99%